2014
DOI: 10.1073/pnas.1407227111
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-B selectively regenerates injured peripheral neurons and restores sensory and trophic functions

Abstract: Significance Peripheral nerve injury is a major neurological disorder that can cause multiple motor and sensory disturbances. In this study we found that VEGF-B can be used as a previously unidentified therapeutic for treating peripheral nerve injury. We demonstrated that VEGF-B stimulated nerve regeneration and enhanced the recovery of both tissue sensation and the ability of nerves to enhance healing of innervated tissue. The physiologic relevance of VEGF-B is demonstrated by our findings showing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 32 publications
8
84
0
1
Order By: Relevance
“…45 Peripheral nerve axon expresses membrane-bound VEGFR1, VEGFR2, and the neuropilin receptors. 8,46 Vascular epithelial growth factor can promote the recovery of injured corneal nerve fibers in anatomical, sensory, and trophic functions, which requires the activation of various VEGF receptors. 9 Here, we also confirmed that bevacizumab injection impaired the regeneration of corneal nerve fibers in normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…45 Peripheral nerve axon expresses membrane-bound VEGFR1, VEGFR2, and the neuropilin receptors. 8,46 Vascular epithelial growth factor can promote the recovery of injured corneal nerve fibers in anatomical, sensory, and trophic functions, which requires the activation of various VEGF receptors. 9 Here, we also confirmed that bevacizumab injection impaired the regeneration of corneal nerve fibers in normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] As a result of these studies, the distribution and architecture of mouse corneal sensory innervation is reasonably well known, confirming that it follows the morphologic pattern of corneal nerve branching described in other mammalian species, 4,5 although remarkable differences exist in nerve density between mice strains. 4 Additionally, the corneal innervation of mice has been used to explore the origin and trophic dependence of peripheral sensory nerves during prenatal development 6 and postinjury nerve regeneration in adults, 3,7,8 as well as age-dependent changes in the architecture and function of corneal nerves. 2,9 Moreover, mice have been extensively employed to define the morphologic alterations of corneal nerves caused by a number of pathologic conditions such as diabetes, 10 surgical injury, 1,11,12 herpes virus infections, 13,14 and dry eye disease.…”
mentioning
confidence: 99%
“…But for use in treatment of corneal neuropathies, VEGA-A has the undesirable potential to stimulate vascular endothelial cells. Thus, it poses a potent angiogenic threat to the avascular cornea [15]. However, VEGF-B has low angiogenic activity, while promoting nerve fiber regeneration.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%